2013
DOI: 10.1080/10401334.2013.797346
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Medicine Clerkship and Ambulatory Learning Experiences: Results of the 2010 Clerkship Directors in Internal Medicine Survey

Abstract: There have been significant increases in the amount of time dedicated to ambulatory internal medicine. The numbers of medical schools with ambulatory internal medicine education has increased. Integration of the ambulatory experiences with other clerkships such as family medicine occurs. Curriculum was varied but difficulties with dissemination and assessment in these disparate settings was noted. Overall, the results of this study demonstrate increased implementation and recognition of the importance of ambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…However, most reports described ambulatory experiences on core clerkships. 33 The most common length was three to four weeks. Our Web site review revealed that an ambulatory care rotation was required during the fourth year by only 47 of the 136 schools (35%).…”
Section: Clinical Experiences In Specific Locationsmentioning
confidence: 99%
“…However, most reports described ambulatory experiences on core clerkships. 33 The most common length was three to four weeks. Our Web site review revealed that an ambulatory care rotation was required during the fourth year by only 47 of the 136 schools (35%).…”
Section: Clinical Experiences In Specific Locationsmentioning
confidence: 99%
“…As patient care has shifted more to outpatient settings, training in outpatient settings has increasingly been prioritized. 4,[8][9][10][11][12] The LCME now stipulates medical schools meet ambulatory learning requirements to ensure trainees are well prepared for outpatient practice. 4 Likewise, the AAMC has outlined competencies that are specific to ambulatory education.…”
Section: Introductionmentioning
confidence: 99%
“…17,22 However, the last national survey by the Clerkship Directors in Internal Medicine (CDIM) evaluating core clerkship IM training occurred in 2010 and in 2008 to evaluate IM sub-internship training. 12,23 These surveys occurred prior to the publication of the CEPAERs, increased focus on ambulatory education, and widespread promotion of LIC's; thus, the degree to which clinical training in IM has changed in response to recent curricular reform efforts is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…11 Internal medicine clerkships evolved from purely in-patient experiences to include roughly 30 % time in clinic today. 12,13 Coincidentally, educators developed improved methods for clinic-based instruction that emphasized 1:1 learner-centered teaching, meaningful student responsibility in patient care, and more supportive learning environments. [12][13][14][15][16][17][18] Although office-based clerkships became popular among students, they were not enough to attract them to primary care specialties.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Coincidentally, educators developed improved methods for clinic-based instruction that emphasized 1:1 learner-centered teaching, meaningful student responsibility in patient care, and more supportive learning environments. [12][13][14][15][16][17][18] Although office-based clerkships became popular among students, they were not enough to attract them to primary care specialties. 9,[19][20][21] In evaluating career options, students place high value on the potential for work satisfaction and a controllable lifestyle.…”
Section: Introductionmentioning
confidence: 99%